Linking bark anatomy to Eucalyptus Physiological Disorder (EPD) in commercial clones - Picoli, Edgard; Jacomini, Franciely; Ladeira, Josimar; Almeida, Maria Naruna; Vidaurre, Graziela; Moulin, Jordão; Zauza, Edival; Guimarães, Lúcio; Isaias, Rosy Mary; Balmant, Kelly; da Costa, Weverton (International Journal of Horticultural Science, 2025)
Abiotic stresses trigger the Eucalyptus Physiological Disorder (EPD) which poses a threat to planted and native stands. This research seeks links between eucalyptus bark histological features and EPD, in which the descriptive bark anatomy and histochemistry are approached. Barks from 5-year eucalyptus trees, from commercial clones of E. grandis, E. urophylla and its hybrids, were collected at breast height (DBH), and 50% and 75% of the commercial height, and evaluated. The eucalyptus bark consisted of a periderm (or rhytidome) and a secondary phloem with conspicuous solitary sieve tube elements (STE). The outer bark revealed a secondary phloem with collapsed STE, whereas its inner counterpart displayed non-collapsed STEs. A region crowded with calcium oxalate (CaOx) crystals in axial parenchyma, covering the non-collapsed and partially overlapped collapsed secondary phloem, was observed. Eucalyptus barks exhibited similar anatomical organization at DBH, 50% and 75% of the commercial height, irrespective of expected EPD phenotype or scores. Notwithstanding, there are qualitative differences that are associated with the proportion of non-collapsed phloem and phloem with crystals, which were higher in the tolerant clones and in trees with score 0. The more resistant clones or samples with lower EPD scores exhibited a higher proportion of the regions of living phloem, phloem with CaOx crystals, and non-collapsed phloem. These results support the hypothesis that an increased proportion of STE collapse will occur concurrently with elevated EPD scores and are the basis for an ongoing histometric approach.